Modeling the Way Strategy to Improve Students' Activities and Abilities in Performing Obligatory Prayers at SD Negeri 18 Aek Batu - Ritonga, Barro; Pohan, Ahir Tua; Ritonga, Hoirunnisa (Program Studi Pendidikan Profesi Guru Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry Banda Aceh, 2023)
This study aims to improve students' activities and abilities in performing obligatory prayers with the Modeling the Way Strategy. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were elementary school students. The data for this study were obtained using test and observation techniques. Tests are used to improve students' activities and abilities in performing obligatory prayers and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that Modeling the Way Strategy Learning can improve students' activities and abilities in performing obligatory prayers. This can be seen from the increase in the percentage of completion of student learning outcomes in each cycle with details of the pre-cycle 47.56%, the first cycle 75.67% and in the second cycle it increased to 88.77%. Thus, the use of the Modeling the Way Strategy can be used as an alternative to improve students' activities and abilities in performing obligatory prayers.